Sources of History of Gastronomy at the Department of Manuscripts in Wroblewski Library of the Lithuanian Academy of Sciences - Danguolė Narkevičienė; Rimvydas Laužikas (Knygotyra)
The article analyzes the sources stored at the Wroblewski Library of the Lithuanian Academy of Sciences, Manuscripts Department, which are significant in the context of the history of Lithuanian gastronomy. In this article, gastronomic culture is viewed as an intangible cultural heritage, and the sources that represent it are period-specific cultural fixations. The article provides a contextual overview of the collection of the Library’s Manuscripts Department. At the time of the research, identified sources were grouped into 8 typological categories. The categories were established based on the content of specific documents informativeness criteria (from the point of view of gastronomic culture and gastronomy history research). This article explains the benefit of each type of manuscript as a source for studies in the history of gastronomy. The list of manuscripts stored at the Wroblewski Library of the Lithuanian Academy of Sciences, Manuscripts Department, identified by the article authors, is presented.